2013
DOI: 10.5946/ce.2013.46.4.337
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Disinfectants for Gastrointestinal Endoscopic Reprocessing

Abstract: Gastrointestinal endoscopy is gaining popularity for diagnostic and therapeutic purposes. However, concerns over endoscope-related nosocomial infections are increasing, together with interest by the general public in safe and efficient endoscopy. For this reason, reprocessing the gastrointestinal endoscope is an important step for effective performance of endoscopy. Disinfectants are essential to the endoscope reprocessing procedure. Before selecting an appropriate disinfectant, their characteristics, limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…The present study results showed that there was minimal compliance for processing of endoscopic accessory equipment. This agrees with the results of another study which found that a third of respondents reported that they reused disposable accessories (12). Reuse of disposable accessories should be avoided so as to limit the likelihood of cross-infection between patients and staff (17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study results showed that there was minimal compliance for processing of endoscopic accessory equipment. This agrees with the results of another study which found that a third of respondents reported that they reused disposable accessories (12). Reuse of disposable accessories should be avoided so as to limit the likelihood of cross-infection between patients and staff (17).…”
Section: Discussionsupporting
confidence: 82%
“…Compliance with national guidelines was achieved for disinfection steps with partial compliance for treatment of the endoscope after disinfection. Another study found that most practitioners complied with the established disinfection guidelines (12), while Seoane-Vazquez and colleagues reported that the primary cause of endoscopy-related infections was poor reprocessing practices (13).…”
Section: Discussionmentioning
confidence: 99%
“…As the characteristics of propofol include a rapid onset of action with a short-term effect, a shorter recovery time, and greater patient and endoscopist satisfaction,22 propofol use may be preferred by endoscopists practicing in primary clinic setting 19. Our survey findings suggested suboptimal performance of endoscopy reprocessing, as 28% of respondents used unapproved disinfectants or did not know main ingredient of their disinfectants as well as 15% to 17% of respondents did not follow reprocessing protocols 23. A Chinese survey from 122 endoscopy units and an Italian survey from 278 endoscopy units also showed significant room for improvement in the practice of endoscopic reprocessing 24,25.…”
Section: Discussionmentioning
confidence: 85%
“…Glutaraldehyde damages DNA (Hopwood, 1975) and compromises the PCR ability of DNA after some days of incubation only (Das et al, 2014). In clinical procedures, an exposure of 20 min at 20 • C in a 2% w/w glutaraldehyde solution is solely used to disinfect medical instruments (Park et al, 2013). We showed that this short incubation time of 20 min was not enough to impact the integrity and PCR ability of DNA.…”
Section: Pure λ Dna Amplification Efficiency Decreased Under Long Micmentioning
confidence: 84%